Evaluation of Financial Performance of the Iraqi Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Insurance Companies perform a prominent role in providing services and bolstering national economy, and they contribute in achieving the aims of the economic development plans in addition to many other social and economic benefits. So it is necessary to evaluate the activity of these companies continuously to define performance level and its nature. Financial analysis is one of the important instruments that helps in analyzing and explanation of data in such a way that enable administration to define performance level and diagnosing strength and weakness points. This study tackles the state of affairs of the Iraqi Insurance Company which is considered as one of the active national institutions, due to its distinguished role in collecting national savings.Different instruments of analyzing are adopted , through which defining and evaluation of performance level could be done.  This study reached to many conclusions and recommendations which help in developing and marketing insurance services and activating its activity in bolestering national economy.